In vitro Cytotoxic Effect of Brazilian Green Propolis on Human Laryngeal Epidermoid Carcinoma (HEp-2) Cells - Bufalo, Michelle C. [UNESP]; Candeias, Joao M. G. [UNESP]; Sforcin, Jose Mauricio [UNESP] (Oxford University Press, 2009)
Propolis is a sticky dark-colored material showing a very complex chemical composition that honeybees collect from plants. It has been used in folk medicine since ancient times, due to several biological properties, such as antimicrobial, anti-inflammatory, antioxidant and immunomodulatory activities, among others. Its antitumor action in vivo and in vitro has also been reported, using propolis extracts or its isolated compounds. The goal of this work was to evaluate propoliss cytotoxic action in vitro on human laryngeal epidermoid carcinoma (Hep-2) cells. These cells were incubated with different concentrations of this bee product for different time periods, and morphology and the number of viable HEp-2 cells analyzed. Data showed that propolis exhibited a cytotoxic effect in vitro against HEp-2 cells, in a dose- and time-dependent way. Propolis solvent had no effects on morphology and number of viable cells, proving that the cytotoxic effects were exclusively due to propolis components. Since humans have been using propolis for a long time, further assays will provide a better comprehension of propoliss antitumor action.
Keywords: antitumor action; HEp-2 cells; propolis